P 94 Integration of audio-visual information in the subthalamic nucleus – evidence from local field potential recordings. Issue 10 (October 2017) - Heldmann, M.; Paracka, L.; Liebrand, M.; Rasche, D.; Tronnier, V.; Krauss, J.; Münte, T.
Abstract : As part of the basal ganglia the subthalamic nucleus is functionally integrated into motoric, limbic, and associative loops connecting the basal ganglia and the prefrontal cortex. Recent recordings from local field potentials have shown, that the human STN is also involved in processing of automatic change detection: sensory changes in a subject's auditory environment result in altered event related local field potentials. Electrophysiological recordings from the STN in rats indicate, that the functional meaning of the STN's responsiveness to sensory inputs could be the integration of sensory and motor information. In the present study we investigated 11 patients suffering from Parkinson's Disease. While performing a task event related local field potentials were recorded from the STN. The task comprised the presentation of standard and rarely occurring deviant stimuli. Stimuli were either monomodal (auditory or visual) or multimodal stimuli (compound stimuli consisting of the stimuli from the monomodal conditions). Patients had to response to the deviant stimuli in one of the sensory domains. The analysis of the event related field potentials indicated a preferred processing of auditory in comparison to visual stimuli in an early time window (100–300 ms). Moreover, in the multimodal condition the presentation of auditory deviants while patients had to respond to a visual deviant had a modulatory effect on the local field potentials' amplitude. These findings suggest that the STN receives and integrates information from different modality most likely in order to use this information in the initiation or withholding of actions.